Theoretical and simulated investigation of dielectric charging effect on a capacitive RF-MEMS switch - Ma, Li Ya; Soin, Norhayati; Nordin, Anis Nurashikin (2016)
Dielectric charges cause stiction problems in most capacitive RF-MEMS switches, creating a major reliability issue during production. A new method based on finite-element- method simulation is developed in this paper to analyze the dielectric charging effect on the RF-MEMS switch’s pull voltages (namely, pull-in and pull-out voltages). The pull voltages have been simulated by using a triangular voltage input; and the actuation time has been obtained by using a step-up bias voltage. The charge effect on the pull voltages due to parasitic charges has been discussed. And the effect of dielectric surface roughness on the switch performance is also deliberated. The study results show that in order to develop a long-lifetime RF-MEMS switch, a small actuation voltage with a flat-dielectric-layer design is preferred. In the end a two-step bipolar rectangular waveform as bias voltage has been proposed additionally for long-lifetime purpose.